Prairie women : images in American and Canadian fiction - Fairbanks, Carol, 1935- (Yale University Press, 1986)
Images of the frontier woman as long-suffering, worn, and alienated from the landscape pervade our historical and literary consciousness. Such images, however, which represent only one aspect of women's lives on the prairies, are most often found in the works of male novelists and historians. This book is based on an examination of over one hundred works from the frontier era to the present, all written by American and Canadian women who lived long periods of their lives on the prairies. The works provide new insights into women's roles on the frontier, their ordeals, and the factors behind their decisions to stay on prairie farms and in prairie towns. The descriptions of relationships between white women and Indians force us to rethink the traditional stereotypes of antagonism and fear on the part of white women and to recognize that some women not only made friends among Indians but preferred the Indian lifestyle. Above all, its vividly demonstrated that many women viewed the prairie with affection: as their home, as a source of imagination and creativity, and for some as a sacred place of healing. -- from book jacket.